Desa Wisata Atau Wisata Desa:Menelaah Fase Kesepian Masyarakat Pasca Pandemi Covid -19 - Sabrina, Maureen Wanda; Harisoesyanti, Kania Saraswati (Jurnal Ilmu Kesejahteraan Sosial, 2023)
The Tourism Village Policy launched by the government has developed into an ambitious initiative that can boost the community's economy. However, behind this dream, there is a complex discussion about how ready the village community is to undertake this transformation. This article discusses the stages of the community undergoing the tourism village program against the background of Taraju Village having limited access, the existence of newly formed supporting community self-help groups, and even the community's initial rejection of the development of a tourism village. Meanwhile, this tourist village has achieved achievements on a provincial and national scale. The research used a qualitative approach with a descriptive design, in-depth interviews, literature studies and field observations. The research results show that in establishing a tourist village, the stage of community readiness is a crucial factor in creating a sustainable tourist village. This stage starts from the reality that there is no public awareness regarding the development of tourism village, so it is necessary to raise awareness from various agencies. Efforts to prepare a tourism village continue with efforts to increase knowledge, as well as village involvement in Tourism Village competitions and culminate in the planning stage for the development of the Taraju Tourism Village.